THE EFFECT OF INTERACTIVE LEARNING MEDIA ON ACTIVITIES AND LEARNING OUTCOME OF SCIENCE - Firmansyah Firmansyah; Syarifuddin Kune; Khaeruddin Khaeruddin (Jurnal Dikdas, 2019)
The problem in this study is the lack of use of instructional media in the classroom. The purpose of this study was to determine the effect of Interactive learning media on student learning activities and outcomes. This research uses quasi experimental design method. This type of research design used is non equivalent control group design. The sample in this study was class V A as experimental class 1 as many as 20 students and class B as experimental 2 as many as 20 students. Analysis of student learning activity data uses the percentage formula and t-test, while the analysis of student learning outcome data uses t-test statistics. The results of data analysis showed the average student learning activities in experimental class 1 using interactive learning media were classified as very active with a percentage value of 82.98%, and the average student learning activities in experimental class 2 with conventional media had a percentage value of 77.2 %. For the t test statistic learning activities show a score of 0.013 <0.05 then the hypothesis is accepted. As for the t test statistics the learning outcomes show a score of 0.007 <0.05 then the hypothesis is accepted. So that it can be concluded that there is an influence of  interactive learning media on the activities and outcomes of science learning.